1997
DOI: 10.1139/g97-027
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mapping of a thermosensitive genetic male sterility gene in rice using bulked segregant analysis

Abstract: The thermosensitive genetic male sterility (TGMS) system is considered to be a more efficient alternative to the cytoplasmic male sterility (CMS) system for hybrid rice. An F2 population from a cross between a TGMS mutant line (IR32364TGMS) and IR68 was used to map the TGMS gene tms3(t). Fertile and sterile bulks were constructed following the classification of F2 plants into true breeding sterile, fertile, and segregating fertile plants based on F3 family studies. From the survey of 389 arbitrary primers in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(47 citation statements)
references
References 19 publications
4
43
0
Order By: Relevance
“…Localization studies showed that the TGMS genes from different sources may be located in different chromosomes. Examples include reports that tms1 (Wang et al, 1995), tms2 (Lopez et al, 2003), tms3 (Subudhi et al, 1997), tms4 (Dong et al, 2000), tms5 (Yang et al, 2007a), rtms1 (Jia et al, 2001), ms-h (Koh et al, 1999), and tms6 (Lee et al, 2005) were located on chromosomes 8, 7, 6, 2, 2, 10, 9, and 5, respectively. However, these TGMS materials are not to be applied in rice production because of the non-stability of their sterility.…”
Section: Genetic Diversity Of Ptgms Ricementioning
confidence: 99%
“…Localization studies showed that the TGMS genes from different sources may be located in different chromosomes. Examples include reports that tms1 (Wang et al, 1995), tms2 (Lopez et al, 2003), tms3 (Subudhi et al, 1997), tms4 (Dong et al, 2000), tms5 (Yang et al, 2007a), rtms1 (Jia et al, 2001), ms-h (Koh et al, 1999), and tms6 (Lee et al, 2005) were located on chromosomes 8, 7, 6, 2, 2, 10, 9, and 5, respectively. However, these TGMS materials are not to be applied in rice production because of the non-stability of their sterility.…”
Section: Genetic Diversity Of Ptgms Ricementioning
confidence: 99%
“…To date, a number of loci that control PGMS or TGMS, including reverse PGMS or reverse TGMS, in different rice lines have been mapped to different chromosomes: photoperiod-sensitive genic male sterile genes pms1 [15,16], pms2 [15], pms3 [17][18][19][20]; reverse photoperiod-sensitive genic male sterile genes rpms1 [21], rpms2 [21]; thermo-sensitive genic male-sterile genes tms1 [22], tms2 [23,24], tms3 [25,26], tms4 [27], tms5 [5,[28][29][30][31], tms6 [32], tms6(t) [33]; photoperiod-thermosensitive genic male sterile genes ptgms2-1 [34], pms1(t) [35]; and reverse thermo-sensitive genic male-sterile genes rtms1 [36]. Despite the wide application of PGMS and TGMS lines in hybrid rice breeding, the genes responsible for PGMS and TGMS in these lines have not been cloned, and the molecular mechanisms underlying these traits remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…It was therefore concluded that pF18 was transferred from the mitochondrion into the nuclear genome. A mapping study indicated that the insertion point was on the short arm of chromosome 6 (Subudhi et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The TGMS mutant line, IR32364TGMS, showed complete male-sterility at day/night temperatures of 32°/24°C but partial fertility at 27°/21°C in an IRRI phytotron. A RAPD marker, OPF18 2600 , amplified by the random primer OPF18 (5-TTCCCGGGTT-3) was found to be linked to tms3 (Subudhi et al, 1997).…”
Section: Plant Materials and Rapd Marker Linked To Tms3mentioning
confidence: 99%
See 1 more Smart Citation